INVESTIGATING THE IMPACT OF PROBLEM BASED LEARNING ON THE TENTH GRADE STUDENTS’ SPEAKING SKILL - Nirmala, Nirna; Monica Peni Utami, Wahyu (FKIP, UNIVERSITAS ISLAM SYEKH-YUSUF TANGERANG, 2024)
Problem-based learning (PBL) is a powerful pedagogical approach which can be effective in ELT. This research aims at finding out the impact of PBL on speaking skill. The population of this research is the tenth-grade students of SMAN 3 Kabupaten Tangerang with the total 500 students. Furthermore, the research was conducted only on 84 students of 10 IPS 5 and 10 IPS 2 as the sample. Quasi-Experimental was employed to answer the research question. Then the research data is collected through pre-test and post-test. The data of this research was statistically calculated by using SPSS 22. The statistical analysis results indicated that the implementation of PBL had a significant impact on the experimental class. However, the statistical test results for the control class did not show any significant difference between the pre-test and post-test scores. Keywords: quasi experimental; problem-based learning; PBL; speaking skill